VD_FINDINFO Décision / 2014 / 521 vom 28. März 2003 - VD Tribunal cantonal (2003)
EXPERTISE PSYCHIATRIQUE, THÉRAPIE, MOTIVATION DE LA DÉCISION, MESUREDROIT PÉNAL, RÉVISIONDÉCISION | 59 CP, 65 al. 1 CP, 65 CP